O anjo de Mensagem - Ramalho, Maria Irene (Pessoa Plural)
This article takes off from Blake’s famous statement about Milton’s Paradise Lost – that Milton wrote in fetters when he wrote about God and the Angels, and in freedom when he wrote about the Devil. The English romantics and Fernando Pessoa agreed. For Pessoa, the Devil is the symbol of imagination and poetry. For these poets, poetry is inevitably on the side of transgression and rebellion, which they link to the Devil as creative energy. The article also wonders about the relationship between Pessoa’s concept of dream and his poetical practice, bringing together A hora do Diabo and Livro do desassossego, where dreaming and non-existing become crucial for poetic creativity.